Advances in Pacific Basin business, economics and finance - Lee, Cheng-Few; Yu, Min-Teh (Advances in Pacific Basin business, economics and finance ;, 2025)
Advances in Pacific Basin Business, Economics and Finance (APBBEF) is a peer-reviewed journal published by Emerald Publishing and is designed to focus on interdisciplinary research in finance, economics, and management among Pacific Rim countries. All articles published are peer-reviewed and recommended by one editorial board member. Topics of interest include, but are not limited to, the following: 1. Policy and management on financial markets and financial institutions; 2. Options, futures, and other derivatives markets; 3. Corporate finance and investment decisions; 4. Insurance and risk management; 5. Accounting, auditing, and taxation; 6. Artificial intelligence and new technology in finance; 7. ESG and sustainability; 8. Income, employment, and education; 9. Monetary and foreign exchange policy; 10. Other economic policies among the Pacific Rim countries.